GDP Growth, Private Debt and Monetary Policy - Gianluca Cafiso (Center for Economic Studies and ifo Institute (CESifo), 2017)
Economic research has considered Private Debt a determinant of GDP growth for years. By keeping this perspective, the objective of this work is to understand how much of the GDP response to a monetary shock is due to the variation of private debt. This is the marginal contribution of private debt, which we relate to an increase of the aggregate demand. We study the USA, the UK and Germany in the period 1980q1-2015q4. Our approach is based on the comparison of one baseline structural VAR with one counterfactual for each country. The analysis is developed using the two main constituents of private debt: households and corporations debt.
Keywords: O11; O16; O51; O52; E44; 330; private debt; GDP; monetary policy; structural VAR